The preparation of teachers of English as an additional language around the world research, policy, curriculum and practice - Polat, Nihat 1974-; Mahalingappa, Laura 1975-; Kayi-Aydar, Hayriye (New perspectives on language and education, 2021)
This book fills a critical gap in a neglected area in current educational research: international teacher education. The chapters focus on the preparation of teachers of English as an additional language (EAL) in established teacher education programs in 11 countries